INOVASI PELAYANAN AKTA KELAHIRAN MELALUI EGOVERNMENT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA YOGYAKARTA - Putri, Eko Kurnia; Pambudi, Argo (Natapraja, 2018)
This research aimed to deeply understand the innovation and the supporting and inhibiting factors innovation of birth certificate service by E-Government. The research design used in this research were descriptive with qualitative approach. The research design was considered able to explain this research in depth. The results showed that the Innovation of Birth Certificate Services by E-Government in Yogyakarta's Department of Population and Civil Registration has not been optimal. It could be seen by the five indicators of innovation of public service according to Rogers advantages, compatibility, complexity, triability, and observability. From those five dimensions, it could be showed that the inovation has not been optimal by these case: 1) the number of users in online birth certificate making service were low, 2) the service innovation offered by the government were numerous, 3) there were no special officers who take care of the online birth certificate making service, 4) the online birth certificate making service was still conducted partially, 5) The citizen's ignorance about the online birth certificate making service. There were also various supporting and inhibiting factors in the innovation of birth certificate making service by e-Government that conducted by the Yogyakarta's Department of Population and Civil Registration.